Evaluation of serial beta-human chorionic gonadotrophin levels after primary treatment of molar pregnancies : can the follow-Up for surveillance of persistence or malignant transformation be shortened? - Hall, Warren J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MMed)--Stellenbosch University, 2012.